Effect of prior steroid treatment on temporal artery biopsy findings in giant cell arteritis. Issue 5 (1st May 2002) - Ray-Chaudhuri, N; Kiné, D Ah; Tijani, S O; Parums, D V; Cartlidge, N; Strong, N P; Dayan, M R
Abstract : Aim: To examine the effect of up to 6 weeks of corticosteroid treatment on the positive temporal artery biopsy rate in giant cell arteritis (GCA). Methods: Prospective comparative clinical study of 11 patients meeting the American College of Rheumatology criteria for diagnosis of GCA. Patients underwent temporal artery biopsy within 1 week, at 2–3 weeks, or after 4 weeks of corticosteroid treatment. Results: Overall, nine of 11 (82%) patients had positive temporal artery biopsies. Six of seven (86%) biopsies performed after 4 or more weeks of steroid treatment were positive. Conclusion: Temporal artery biopsy is useful several weeks after institution of steroids.